Confessions of an economic hit man - Perkins, John. (San Francisco Berrett-Koehler Publishers, 2004)
As an Economic Hitman (EHM), John Perkins helped further American imperial interests in countries such as Ecuador, Panama, Indonesia and Saudi Arabia. As Chief Economist for the international consulting firm Chas. T. Main, he convinced underdeveloped countries to accept massive loans for infrastructure development and ensured that the projects were contracted to multinational corporations. The countries acquired enormous debt, and the US and international aid agencies were able to control their economies.
Includes bibliographical references and index.
Keywords: Perkins, John, 1945-